Digital Pedagogy Policy in Technical and Vocational Education and Training (TVET) in Malaysia: Fuzzy Delphi Approach - Mohd. Jamil, Mohd. Ridhuan; Mohamed Hasyim, Abdul Talib; Othman, Mohd. Syaubari; Ahmad, Abdul Muqsith; Mat Noh, Nurul Rabihah; Mustaffa Kamal, Mohd. Firdauss (Journal of Technical Education and Training, 2023)
Digital platforms are one of the technology adoption that is beginning to be used in most vocational colleges today. Services provided through digital platforms are an alternative to conventional methods. However, the use of digital platforms nowadays, among users consisting of vocational college students in Malaysia is still at a less than satisfactory level. Previous studies also focused a lot on the use and acceptance of technology platforms among users in schools only but not in vocational colleges (VC). The aim of the research is to determine the experts’ consensus on the objective of the digital pedagogy policy for Technical Education and Vocational Training (TVET) students especially in vocational colleges which is currently under development. Vocational colleges is one of the Technical Education and Vocational Training (TVET) institutions in Malaysia that offers certificate level and skill diploma education to high school students. Therefore, it is important to identify the policy that will be used. The Fuzzy Delphi Technique (FDT) was used in this research. Ten experts were chosen by utilizing the purposive sampling method. Analysis of the data was using the Triangular Fuzzy Number and Defuzzification process. The findings showed 100% consensus was achieved by the experts for objectives 1 and 3, and 90% consensus was achieved by the experts for objective 2. All of the experts agreed on the elements in the objectives of the digital pedagogy policy for TVET students. Further development of this policy hopefully will help the teachers in improving their knowledge of digital pedagogy and increase their competency pedagogy in order to produce skills oriented workforce among TVET students in Malaysia. Therefore, the results of this study are expected to be used to strengthen the development of e-learning models in the future to help students and educators to use digital platforms in vocational colleges in particular.